Autologous Costal Cartilage Harvest for Rhinoplasty with Simultaneous Breast Surgery: A Safe and Efficient Technique. (20th January 2020) - Calvert, Jay W; Rovelo, Millicent O; Orlando, Marc V; Kwon, Edwin
Abstract: Background: Autologous costal cartilage is frequently required for revision rhinoplasties and for challenging primary rhinoplasties. Patients undergoing a concomitant breast surgery can have costal cartilage harvested through their breast surgery incisions, thereby obviating an additional rib harvest scar. The safety and efficacy of this approach has yet to be described. Objectives: The aim of this study was to evaluate the outcomes, safety, and results of a new technique, described here, for harvesting costal cartilage during a concomitant breast operation. Specifically, the rates of capsular contracture and rhinoplasty revisions were of great interest. Methods: A retrospective review was performed evaluating the senior author's experience with this technique. Data collected included patient demographics, operations performed, operative time, perioperative morbidity, and postoperative complications. Rates of capsular contracture and rhinoplasty revisions were compared with national averages. Results: A total of 31 female patients were included. Ten (32.3%) breast complications occurred. There were 6 (19.4%) rhinoplasty complications, comprising 1 infection and 5 revisions. The capsular contracture rate was 6% and the rhinoplasty revision rate was 16%. Both of these rates are comparable to independent breast surgeries and rhinoplasties. There were no cases of perioperative mortality or major morbidity. Conclusions: Combining breast surgery and rhinoplasty surgery allows for autologous rib harvest through the breast surgery incisions. This is a safe technique that results in outcomes similar to either procedure performed alone. In addition, the patient is spared an additional surgery and donor site scar. Level of Evidence: 4: